CFDA-AM staining to assess the metabolic activity of Giardia duodenalis cysts inactivated by chlorine, boiling and ultraviolet irradiation. (4th August 2022) - Rodrigues da Cunha, Maria Júlia; Souza Freitas, Bárbara Luíza; Nasser Fava, Natália de Melo; Sabogal-Paz, Lyda Patricia
Abstract: Giardia duodenalis is responsible for several waterborne gastrointestinal outbreaks worldwide. In addition to limitations presented by the main disinfection methods, assessing the inactivation efficiency of cysts after the treatment also poses challenges. Thus, this study aimed to use the 5-carboxyfluorescein diacetate acetoxymethyl ester (CFDA-AM) staining protocol to evaluate the viability of G. duodenalis cysts inactivated by different UV and chlorination doses and boiling times. Under epifluorescent microscopy, metabolically active cysts that presented green fluorescence were considered viable. In contrast, when no green fluorescence could be observed, organisms were considered non-viable. Although statistical analysis revealed that increasing the UV dose did not significantly decrease the percentage of viable cysts, the fluorescence signal intensity decreased considerably when the cysts were irradiated with a dose equal to or greater than 80 mJ cm −2 . Regarding chlorination and boiling treatments, this study demonstrated that no cyst showed fluorescence at the lowest NaClO concentration (0.5 mg/L) and in the shortest boiling time (2 min). Despite some limitations regarding the use of metabolic activity as a viability marker, this methodology is rapid, easy to run and cost-effective. Thus, we conclude that the CFDA-AM staining protocol has the potential to be used to assess Giardia cyst inactivation, although further research is required. HIGHLIGHTS: 5-Carboxyfluorescein diacetate acetoxymethyl ester (CFDA-AM) dye is efficient as a metabolic activity marker of G. duodenalis cysts. The CFDA-AM staining protocol is not the most indicated to assess cell viability after UV irradiation disinfection. No cyst showed metabolic activity at the lowest NaClO concentration and in the shortest boiling time. The CFDA-AM staining protocol is suitable to assess the inactivation of cysts in chlorination and boiling-based water treatment. Graphical Abstract